Evaluation of three different antigens in an indirect enzyme-linked immunoassay for the detection of antibodies against Brucella abortus SRB51 in vaccinated heifers - Robles, Carlos Alejandro; Nielsen, Klaus; Gall, David; Willems, Priscila Mabel (Elsevier, 2022)
The live attenuated Brucella abortus SRB51 (SRB51) is a partial O-chain-deprived mutant. The relative lack of the polysaccharide prevents it from inducing antibodies detectable by most of the serological tests used for the diagnosis of bovine brucellosis. The performance of three antigens used in an indirect enzyme-linked immunoassay test for detecting SRB51 antibodies were evaluated. A homogeneous group of twenty-five 10-month-old Hereford heifers was used. The animals were bled on day 0 and then subcutaneously vaccinated with 2 ml of a commercially available SRB51 vaccine (Schering-PloughTM) containing 1 107 to 3.4 107 viable cells. Blood samples without anticoagulant for sera obtaining were then collected at days 30, 90, 210 and 360 post-vaccination. To detect the SRB51 antibodies, Brucella ovis hot saline extract, B. ovis RLPS (RLPS), and SRB51-RLPS were used. The buffered antigen plate agglutination test and an indirect enzyme-linked immunoassay (I-ELISA) using the smooth LPS (SLPS) antigen from B. abortus were used as control tests. All the sera samples were negative in the BPA test and in the standard I-ELISA using the SLPS. The SRB51-RLPS and the B. ovis RLPS antigens performed better than the B. ovis hot saline extract antigen.